2001
DOI: 10.1556/aphysiol.88.2001.3-4.7
|View full text |Cite
|
Sign up to set email alerts
|

Body composition and peak aerobic power in male international level Hungarian athletes

Abstract: Body size, physique, body composition and physiological performance of elite athletes are independent aspects, have aroused the interest of exercise scientists, but studies that combine these aspects in elite athletes are scarcely available. The aim of the present study was to describe the selected anthropometric and exercise physiological characteristics of some Hungarian top athletes. The investigated subjects were qualified Hungarian water polo players (n=25), paddlers (n=24) and modem pentathlonists (n=20)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 7 publications
2
12
0
1
Order By: Relevance
“…This measurement is an indication of a significant difference between the players of two teams in terms of the amount of subcutaneous fat. The fat percentage of Spanish players are similar and the same parameter value of Iranian are higher than previous published [20] however the fat percentage of Iranian players are similar with published [21][22][23]. Comparing these values suggests that Iranian players' total subcutaneous fat is higher than their international peers.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This measurement is an indication of a significant difference between the players of two teams in terms of the amount of subcutaneous fat. The fat percentage of Spanish players are similar and the same parameter value of Iranian are higher than previous published [20] however the fat percentage of Iranian players are similar with published [21][22][23]. Comparing these values suggests that Iranian players' total subcutaneous fat is higher than their international peers.…”
Section: Discussionsupporting
confidence: 79%
“…So the valued who reported in other published showed that the stature value of Iranian team are in line with the national Greek team [26]. As all fitness experts know, taller height and a more or less heavy body is the most important factors for athlete's performance [20]. Therefore, it can be concluded that despite of that two groups weight are equal and more subcutaneous fat is in Iranian players as well as higher stature of the Spanish, in contrast to the Iranians, the Spanish players have more muscular bodies, taller stature and lower fat percentage which is an advantage for them.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Tsekouras et al (2005) found VO 2max values of Greece water polo players as 57.9±7 ml/kg/min after 400 m swim, and heart rate after test as 174±6 beat/min. Frenkl et al (2001) determined VO 2max values of water polo players at elite level in their study in Hungary carried out with athletes of various branches with the treadmill as 59.7±4.9 ml/kg/min, and heart rate after test as 185.05±5.4 beat/min. Rodriguez (1997) found VO 2max values of swimmers and water polo players on bicycle ergo meter as 57.5 ml/kg/min, heart rate after test as 188.7 beat/min.…”
Section: Aerobic Capacity Testmentioning
confidence: 99%
“…Having specific body size undoubtably gives great advantage in terms of skills (Svantesson et al 2008), Frenkl et al 2001). Around the world, in studies dealing with anthropometric features around the world, the most highly debated issues include which body profiles are more suitable for which branches and the importance degree of this feature in terms of aptitude eliminations for underwater sports (Svantesson et al 2008), Sogut et al 2004).…”
Section: Introductionmentioning
confidence: 99%